Pashahyī folklor - Lāmwāl, ʻAbd al-Mālik (Da Kultur Dawlatī Kumītah, da khalgo [sic] Farlang Riyāsat, da khalgo [sic] Farhang Amiriyat, 1986)
On the folklore of Pashans, a tribe from the Nangarhar, Afghanistan.